Gallium Nitride Metalens for Image Decryption - Meng-Hsin Chen (MDPI AG, 2021)
As the demand for secure digital data continues to increase, image encryption and decryption have recently received tremendous attention. The rapid development of ultrathin metasurfaces has mainly been driven by the desire for the introduction of novel methods with which electromagnetic waves can be manipulated. As a promising application of metasurfaces, metalenses have shown great potential to replace bulky traditional optical devices. In this work, we present that the images produced by a commercially available projector are encrypted by using the color superposition principle, and the fabricated metalens is subsequently utilized to perform image decryption with an incidence made of white light-emitting diodes (LEDs). The correct positions for image decryption are carefully found by three distinct diode lasers as incident light sources. Recent investigations show that high-performance metalenses can be successfully developed once the suitable dielectric material is chosen. As a consequence, our metalens of high performance is composed of hexagon-resonated elements (HREs) made of gallium nitride (GaN) and is capable of resolving line width as small as 870 nm. The metalens with a smaller diameter of 8 μm is numerically simulated with a diffraction-limited focusing efficiency as high as 92%. This work once again shows that GaN metalenses, as future optics, have great prospects in expanding widespread applications in the near future.